Ranking Of Total Quality Management’s Critical Techniques In The Malaysian Automotive Industry - Azizi, Amir (2007)
Today all organizations around the world are trying to optimize the business process in the global market upon continuous improvement and total quality management in order to survive in a competitive market. Since there are huge costs to implement all tools and techniques of total quality management and it is not economical for any organization to apply all. Nine Total Quality Management’s Critical Techniques (TQM’s CTs) have been presented to implement in automotive industry. Each technique has a special application but on the other hand, some of them can be used for an assimilation objective and also some of them can be applied for more than one objective. The main objective of this study has been based on both internal and external customer satisfaction. In order to achieve the main objective, six significant criteria as decision making parameters have been proposed. The study has ranked the TQM’s CTs as alternatives regarding to each criterion through one of the best and widely used decision making methods that is called Analytic Hierarchy Process (AHP) in ten selected Malaysia automotive companies. It has also determined an overall ranking of implementation of TQM’s CTs with respect to all criteria and by considering their performance weight. The results of overall ranking of TQM’s CTs are listed as follows: (1) Advanced Product Quality Planning Process (APQP); (2) Quality Function Deployment (QFD); (3) Failure Mode and Effect Analysis (FMEA); (4) Production Part Approval Process (PPAP); (5) Statistical Process Control (SPC); (6) Measurement Systems Analysis (MSA); (7) Management and Planning (MP) tools; (8) Kaizen; (9) 5S. It has also been found the weight of relationship of TQM’s CTs. For example, FMEA and SPC, QFD and APQP, QFD and FMEA, and 5S and Kaizen have highest relationship rather than other critical techniques of TQM. Finally, an integrated implementation framework of the TQM’s CTs with respect to their both relationship and performance weight has been suggested to create awareness and to guide quality planning managers to have an effective implementation of theses critical techniques of TQM.